Sexual Capital - Alexander Pavlov (Journal of Economic Sociology, 2023)
Academic research on sexuality spans various disciplines, including sexology, sex research, critical sexuality studies, representations of sexuality in the media, gender studies, and sexual identity studies, among others. When it comes to the sociological study of sexuality, sociologists typically either engage in anthropological or narrowly sociological studies of social communities and spaces or conduct macroanalyses, as exemplified by Anthony Giddens in The Transformation of Intimacy (1992). In the 21st century, building on the sociological theory of Pierre Bourdieu, some sociologists have begun to develop the concept of “sexual capital,” viewing sex and sexuality as integral aspects of collective social life. This paper identifies and describes three sociological theories of sexual capital: “erotic capital” (Catherine Hakim); the theory of sexual fields (Adam Isaiah Green and others), in which sexual capital operates alongside other elements such as erotic habitus and practice; and “neoliberal sexual capital” (Eva Illouz and Dana Kaplan). Particular emphasis is placed on the latter theory, as it was introduced relatively recently. In the era of neoliberalism, where the precariat is constantly searching for opportunities in a highly competitive labor market, to feel masterfully becomes crucial . “Neoliberal sexual capital” facilitates this for several reasons: firstly, it boosts self-esteem; secondly, it implies dominance; thirdly, it can serve as a means to demonstrate social competence, and fourthly, it contributes to greater job satisfaction. Recognizing that discussions about sexual capital have only recently started to gain momentum, the author of this review paper presents these theories as competitors within the academic field of sociology.